2018
DOI: 10.1038/s41598-018-35265-y
|View full text |Cite
|
Sign up to set email alerts
|

The discovered chimeric protein plays the cohesive role to maintain scallop byssal root structural integrity

Abstract: Adhesion is essential for many marine sessile organisms. Unraveling the compositions and assembly of marine bioadheisves is the fundamental to understand their physiological roles. Despite the remarkable diversity of animal bioadhesion, our understanding of this biological process remains limited to only a few animal lineages, leaving the majority of lineages remain enigmatic. Our previous study demonstrated that scallop byssus had distinct protein composition and unusual assembly mechanism apart from mussels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…After removing potential transmembrane or cytosolic proteins, a total of 186 BRPs with signal peptide were eventually remained and regarded as the byssal secretome ( Table S3 ), which covered 87.5% of the reported adhesive proteins in C. farreri detected by mass spectrometry ( Fig. S1 a) [17] , [19] , [21] , [65] . The two exceptional adhesive proteins either had low expression level (CF54475.1, average TPM = 6.82) or none predicted signal peptide (CF23353.17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing potential transmembrane or cytosolic proteins, a total of 186 BRPs with signal peptide were eventually remained and regarded as the byssal secretome ( Table S3 ), which covered 87.5% of the reported adhesive proteins in C. farreri detected by mass spectrometry ( Fig. S1 a) [17] , [19] , [21] , [65] . The two exceptional adhesive proteins either had low expression level (CF54475.1, average TPM = 6.82) or none predicted signal peptide (CF23353.17).…”
Section: Resultsmentioning
confidence: 99%
“…We searched all the reported marine adhesive proteins identified from the bioadhesives of eight representitive marine adhesive organisms from published papers [17] , [19] , [20] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] . According to the accession ID provided in these papers, we downloaded the protein sequences from NCBI or UNIPROT [45] , [46] with no more inclusion or exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…How bivalve BRPs were originated and evolved is intriguing, and a recent study provides some insights into this puzzle. Xu et al (2018) focused on a novel scallop BRP (named Sbp9), which was discovered from byssal root and contains repetitive calcium-binding domain (CBD) and tandem epidermal growth factor-like domains. They found that Sbp9 represents a chimeric gene probably resulting from a gene fusion event through the acquisition of CBD2 domain by tenascin like gene from Na+/Ca2+ exchanger 1 gene.…”
Section: Foot Secretome and Evolutionmentioning
confidence: 99%
“…Scallop Chlamys farreri is able to firmly attach to a substrate using its byssus even in dynamic marine environment 28 . Scallop byssus possess high strength that can bear more than 100 times of its own body weight 29 . Another notable feature is that the byssal thread shows extraordinary extensibility, stretching more than twice of its original length (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their attractive mechanical properties, little is known about the components and molecular assembly mechanisms of the scallop byssus. We previously identified the major components and distribution of scallop byssal proteins (Sbps) by combining transcriptomics and proteomics 29 32 . The byssus is composed of more than 20 different proteins and mucopolysaccharides 28 , 30 , 31 , 33 .…”
Section: Introductionmentioning
confidence: 99%